Preparing UK tennis academy players for the junior-to-senior transition: Development, implementation, and evaluation of an intervention program - Pummell, E. K. L.; Lavallee, D. (Psychology of Sport and Exercise, 2019)
Objectives: The current case study aimed to develop, implement and evaluate an intervention program to aid preparation for the junior-to-senior transition (JST) in sport, which provides a novel contribution to the existing professional practice literature. The program, based upon existing theory, focused on developing resources, knowledge and readiness to cope with the transition. The authors were particularly interested in exploring the participants' evaluations. Design/Method: A symbolic modeling approach was adopted, in which 5 senior tennis players were recorded on video discussing the demands of and coping strategies for the JST. The videos were used to support the intervention and delivered over 11 weeks to 7 junior tennis players from an elite training program in the U.K. (M?=?15.1 years, SD?=?1.24). To evaluate the intervention, a mixed methods single-subject design was used, with readiness to cope, knowledge and athletic identity assessed at three time points, along with social validation. Results: Social-validation data indicated that the participants placed value on the intervention as a means to prepare for transition, citing increases in knowledge, coping, confidence and transition related skills. Quantitative data demonstrated an increase in readiness to cope with, and an increase knowledge of the JST. Athletic identity showed a small decrease. Conclusions: The current study supports existing research upon the value of preparation for transition in sport, with this the first transition preparation program for the JST well received by athletes. Further research is required to explore longitudinally how such interventions contribute to a successful JST.